Using Simmental bulls on Hereford cows - M. McKee; R.R. Schalles; K.O. Zoellner (Kansas Agricultural Experiment Station Research Reports, 1970)
Fourteen registered Hereford cows in the Kansas State University purebred teaching herd were mated artificially to the Simmental bull Capitaine #1236 in November and December, 1968. The 23 ampules of semen available were used on the first 23 Hereford cows to show estrus following November 20, 1968. Of cows inseminated, six calved as two-year olds, two as three-year olds, one at four years, two at five years, one at eight, and two at ten years of age. The two that calved at five years of age were sold prior to calving. Both calved unassisted but one calf was dead at birth. Only three of the remaining 12 cows calved unassisted. Some of those assisted might have calved unassisted. Early results indicated assistance was good management, as soon as it appeared to be needed.
Keywords: Cattlemen' s Day; 1970; Report of progress (Kansas State University. Agricultural Experiment Station); 536; Beef; Simmental; Hereford; Artificial insemination